2009
DOI: 10.1523/jneurosci.2132-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic and Postsynaptic Interaction of the Amyloid Precursor Protein Promotes Peripheral and Central Synaptogenesis

Abstract: A critical role of the amyloid precursor protein (APP) in Alzheimer's disease (AD) pathogenesis has been well established. However, the physiological function of APP remains elusive and much debated. We reported previously that the APP family of proteins is essential in mediating the developing neuromuscular synapse. In the current study, we created a conditional allele of APP and deleted APP in presynaptic motor neuron or postsynaptic muscle. Crossing these alleles onto the APP-like protein 2-null background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
256
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(284 citation statements)
references
References 48 publications
16
256
2
1
Order By: Relevance
“…A growing number of studies have documented abnormal electrical activity in APP-transgenic models for Alzheimer's disease (Lalonde et al, 2005;Palop et al, 2007;Westmark et al, 2008;Minkeviciene et al, 2009;Ziyatdinova et al, 2011;Corbett et al, 2013). These models differ in the APP mutations they encode, the coexpressed transgenes, and the promoters used to drive expression.…”
Section: Tet-off App Mice Display Eeg Abnormalities Similar To Other mentioning
confidence: 99%
See 3 more Smart Citations
“…A growing number of studies have documented abnormal electrical activity in APP-transgenic models for Alzheimer's disease (Lalonde et al, 2005;Palop et al, 2007;Westmark et al, 2008;Minkeviciene et al, 2009;Ziyatdinova et al, 2011;Corbett et al, 2013). These models differ in the APP mutations they encode, the coexpressed transgenes, and the promoters used to drive expression.…”
Section: Tet-off App Mice Display Eeg Abnormalities Similar To Other mentioning
confidence: 99%
“…Because the tet-off APP mice exhibit spontaneous EEG abnormalities, we wanted to test whether they were also more vulnerable to chemically induced seizures, as demonstrated for other APPtransgenic models (Del Vecchio et al, 2004;Palop et al, 2007;Westmark et al, 2008). We implanted APP/TTA and control animals with transmitters at 6 -7 months of age to monitor the seizure induction both electrographically and behaviorally.…”
Section: Increased Susceptibility To Chemically Induced Seizures Is Nmentioning
confidence: 99%
See 2 more Smart Citations
“…APP can participate in transmembrane signaling events due to its highly conserved extracellular and intracellular domains, which plays important roles in many physiological processes [3][4][5][6][7]. Many recent studies have indicated that APP is overexpressed commonly in solid tumors and mainly involved in promoting proliferation of tumor cells, including oral squamous cell carcinoma [8], pancreatic cancer cells [9], parathyroid tumor [10], and breast cancer [11].…”
Section: Abstract: App Kasumi-1 Aml1/eto Panobinostatmentioning
confidence: 99%